Placental Cord Insertion Distance From the Placental Margin and Its Association With Adverse Perinatal Outcomes. Issue 5 (May 2021) - Bigelow, Catherine A.; Robles, Brittany N.; Pan, Stephanie; Overbey, Jessica; Robin, Esther; Melamed, Alexander; Bianco, Angela; Mella, Maria Teresa
Abstract : (Abstracted from Eur J Obstet Gynecol Reprod Biol 2020;255:51–55) Detection of an abnormal placental cord insertion (PCI)—either marginal or velamentous—can be assessed in the midtrimester. Marginal PCIs are defined as occurring at a distance of <2 cm from the placental edge; velamentous PCIs occur when the placental cord inserts into the fetal membrane.